2015
DOI: 10.1111/hae.12796
|View full text |Cite
|
Sign up to set email alerts
|

Association between bleeding tendency and health‐related quality of life in carriers of moderate and severe haemophilia

Abstract: We conclude that the subgroup of carriers of haemophilia with increased bleeding tendency have impaired HRQOL. The SF-36 results indicate that this condition affects mental rather than physical health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
0
18
0
1
Order By: Relevance
“…These results suggest that the Self‐BAT is a promising screening tool for bleeding and warrants testing in other bleeding disorder populations, such as haemophilia carriers. Additionally, research has shown that quality of life, especially mental health, is diminished for haemophilia carriers . This is an important measure when assessing well‐being and treatment efficacy.…”
Section: Includes Information On All Haemophilia Carriers Enrolled (Nmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that the Self‐BAT is a promising screening tool for bleeding and warrants testing in other bleeding disorder populations, such as haemophilia carriers. Additionally, research has shown that quality of life, especially mental health, is diminished for haemophilia carriers . This is an important measure when assessing well‐being and treatment efficacy.…”
Section: Includes Information On All Haemophilia Carriers Enrolled (Nmentioning
confidence: 99%
“…Additionally, research has shown that quality of life, especially mental health, is diminished for haemophilia carriers. 8 This is an important measure when assessing well-being and treatment efficacy.…”
Section: Evaluation Of the Self-administered Bleeding Assessment Toolmentioning
confidence: 99%
“…Women who are carriers of hemophilia are usually without bleeding symptoms. Carriers with bleeding symptoms may experience inappropriate care, feel mistrusted and not taken seriously by the healthcare system (Renault et al 2011), and have impaired health-related quality of life (Olsson et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown an increased risk of bleeding among carriers compared with women without bleeding disorders. The bleeding symptoms typically include menorrhagia and/or excessive bleeding in association with pregnancy and delivery and reduced health‐related quality of life (HRQL) . Importantly, bleeding symptoms may also occur among those with normal factor activity and the phenotype seems only partially correlated with the factor activity .…”
Section: Introductionmentioning
confidence: 99%